Influence of the Oriented Configuration of the BarChip Fibre Polypropylene to the Ductility Factor of the Reinforced Concrete Beam - Daniel RT Siregar; Koswara Koswara; Syahril Taufik (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract Bending and shear strength of fiber reinforced polimer concrete beams was studied in this research project. The reinforced concrete beam behaves in brittle structure in the certain reinforcement configuration. BarChip fibre polypropylene as the material for enhancement of the ductility factor is applied to the concrete beam. Three types of BarChip fibre configuration were examined: randomly spreading, placing at the mid-span area, and concentration on the tension zone. The experimental program included five beam specimens. Two of the beams were control specimens in which one was reinforced with no fibre, while the other one did not have any Barchips polypropylene. Each one of the other three specimens was reinforced with one of the above mentioned fibers by 0,4% volumetric ratio. Investigating the following issues for medium-high concrete strength was the goal of this study. In order to determine whether adding 0.4% volumetric ratio of polypropylenes as additional bar reinforcement in beams would provide adequate strength and stiffness properties comparable to reinforcing steel used as minimum bar reinforcement, it was necessary to first assess the effectiveness of each type of oriented fiber configuration on the bending strength, then to look into each beam's bending strength, shear strength, toughness, crack patterns, and near ultimate load crack width. The findings demonstrated that the bending capacity of the beam specimens was raised by all three types of polypropylene configuration more than by the beam reinforced with the fewest amount of bar reinforcement. Additionally, some of the employed fibers may cause failures other than pure shear. It is reccomended to spread the polypropylene within the tension zone of the reinforced concrete beam on the bottom mid span. Keywords: Fibrous Concrete, Polypropylene, Ductility, Reinforced, Beam